Açaí berries (Euterpe oleracea Mart.) dried extract improves ethanol‐induced ulcer in rats. (19th May 2020) - Cury, Benhur Judah; Boeing, Thaise; Somensi, Lincon Bordignon; Mariano, Luisa Nathália Bolda; de Andrade, Sergio Faloni; Breviglieri, Eduardo; Klein‐Junior, Luiz Carlos; de Souza, Priscila; da Silva, Luisa Mota
Abstract: Objectives: Açaí ( Euterpe oleracea ) is widely consumed in Brazil and known for its numerous health‐beneficial properties. This study investigated the gastroprotective potential of the dried açaí berries extract (DAE). Methods: Dried açaí berries extract effect was evaluated against ethanol‐induced gastric ulcer in rats. Its ability to regulate antioxidant defenses and reduce inflammatory parameters was evaluated in the ulcerated tissues. The scavenger capability of DAE was assessed by DPPH assay, and phytochemical composition was accessed by UHPLC. Key findings: The extract showed radical scavenger activity in vitro (IC50  = 210 µg/ml) and gastroprotective effect in vivo, reducing the ulcerated area by 83%, 67% and 48% at doses of 30 and 100 mg/kg (p.o) and 3 mg/kg (i.p), respectively, compared with vehicle group. Besides, DAE (100 mg/kg, p.o) increased the GSH content and GST activity in ulcerated mucosa. Animals treated with DAE showed normalized levels of SOD activity, elevated CAT activity and decreased MPO activity, as well as reduced TNF‐α levels, compared with vehicle group. Peonidin‐3‐glucoside, peonidin‐3‐rutinoside, cyanidin‐3, 5‐hexoside‐pentoside, cyaniding‐3‐glucoside, pelargonidin‐3‐glucoside and pelargonidin‐3‐rutinoside were identified in DAE. Conclusions: Our findings suggest that DAE reduces the inflammation and maintains the oxidative balance of gastric mucosa, therefore being a promising natural resource or useful nutraceutical to protect gastric mucosa.